2022
DOI: 10.1038/s41467-022-32233-z
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-deep sequencing validates safety of CRISPR/Cas9 genome editing in human hematopoietic stem and progenitor cells

Abstract: As CRISPR-based therapies enter the clinic, evaluation of safety remains a critical and active area of study. Here, we employ a clinical next generation sequencing (NGS) workflow to achieve high sequencing depth and detect ultra-low frequency variants across exons of genes associated with cancer, all exons, and genome wide. In three separate primary human hematopoietic stem and progenitor cell (HSPC) donors assessed in technical triplicates, we electroporated high-fidelity Cas9 protein targeted to three loci (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 47 publications
0
35
0
Order By: Relevance
“…5b ). Additionally, unlike prior studies that relied on a pre-existing pool of cells with oncogenic mutations 36,37 , by conducting our experiments in primary HSPCs that do not harbor such aberrations 38 , it is not surprising that this study found no bona fide OT sites residing in exons of known tumor suppressors or oncogenes. This was further confirmed by a recent publication that found no evidence that Cas9 introduced or enriched for oncogenic mutations following ex vivo editing in primary HSPCs 38 .…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…5b ). Additionally, unlike prior studies that relied on a pre-existing pool of cells with oncogenic mutations 36,37 , by conducting our experiments in primary HSPCs that do not harbor such aberrations 38 , it is not surprising that this study found no bona fide OT sites residing in exons of known tumor suppressors or oncogenes. This was further confirmed by a recent publication that found no evidence that Cas9 introduced or enriched for oncogenic mutations following ex vivo editing in primary HSPCs 38 .…”
Section: Discussionmentioning
confidence: 70%
“…Additionally, unlike prior studies that relied on a pre-existing pool of cells with oncogenic mutations 36,37 , by conducting our experiments in primary HSPCs that do not harbor such aberrations 38 , it is not surprising that this study found no bona fide OT sites residing in exons of known tumor suppressors or oncogenes. This was further confirmed by a recent publication that found no evidence that Cas9 introduced or enriched for oncogenic mutations following ex vivo editing in primary HSPCs 38 . Taken together, our study highlights the importance of evaluating Cas9 OT detection tool performance in the appropriate application-specific context (e.g., high-fidelity nuclease, primary HSPCs) where epigenetic factors and DNA damage repair mechanisms can impact the appearance of unwanted OT editing.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…These methods vary widely in their approach and even starting material, using cell-free genomic DNA in vitro ( Kim et al, 2015 ; Cameron et al, 2017 ; Tsai et al, 2017 ; Kim and Kim, 2018 ; Lazzarotto et al, 2020 ; Dobbs et al, 2022 ), in intact live cells ex vivo ( Crosetto et al, 2013 ; Tsai et al, 2015 ; Yan et al, 2017 ; Wienert et al, 2019 , 2020 ; Zhu et al, 2019 ), and in vivo animal models ( Akcakaya et al, 2018 ; Wienert et al, 2019 ; Liang et al, 2022 ). Methods that use cell- and nucleosome-free DNA generally report the highest number of off-targets, many of which cannot be verified in a cellular context ( Cromer et al, 2022a ). Furthermore, methods such as GUIDE-Seq have been shown to identify more off-target sites in immortalized cell lines than when assaying primary cells ( Shapiro et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…(3) Evaluating indels alone may also miss complex DNA damage outcomes such as large deletions and translocations [8,39]. Furthermore, deep amplicon sequencing may miss rarer off-target sites due to a lack of enrichment of altered DNA molecules and insufficient sequencing depth [40]. For all these reasons, enrichment for sites with evidence of CRISPR-induced DNA damage is a more holistic readout of offtarget activity than indels alone.…”
Section: Discussionmentioning
confidence: 99%